2018
DOI: 10.1016/j.earlhumdev.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mental health during the neonatal period: Relationships to the occupation of parenting

Abstract: Although parents of very preterm infants have higher rates of maternal mental health challenges, mothers of full-term infants at high social risk are also impacted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 70 publications
1
55
0
1
Order By: Relevance
“…This phenomenon can be explained by the urban effect where half of the urban impact was described by wealth and education alone [33,34]. In a study conducted in Mumbai, India also found out the customs as per ethnicity or religion to influence the uptake of maternal health care services, which were similar to our study [35][36][37].…”
Section: Discussionsupporting
confidence: 85%
“…This phenomenon can be explained by the urban effect where half of the urban impact was described by wealth and education alone [33,34]. In a study conducted in Mumbai, India also found out the customs as per ethnicity or religion to influence the uptake of maternal health care services, which were similar to our study [35][36][37].…”
Section: Discussionsupporting
confidence: 85%
“…The transition of care from NICU to home can be challenging (Aagaard et al, 2015;Blackburn & Harvey, 2019;Harris et al, 2018;Majoli et al, 2019;Pineda, Bender, et al, 2018;Purdy et al, 2015).…”
Section: Review Of Evidencementioning
confidence: 99%
“…The transition of care from NICU to home can be challenging (Aagaard et al, 2015; Blackburn & Harvey, 2019; Harris et al, 2018; Majoli et al, 2019; Pineda, Bender, et al, 2018; Purdy et al, 2015). While certain sociodemographic factors may affect parenting behaviors and choices in relation to therapy services after NICU discharge (Clements et al, 2008), the timing of interventions and the dynamics surrounding a young infant after discharge from the NICU may further impede access.…”
Section: Introductionmentioning
confidence: 99%
“…12,17,29,32 In several studies, socioeconomic advantage was found to facilitate higher rates of parental presence. 12,18,25,30 However, evidence for other barriers to presence was often mixed; for example, increased gestational age, increased birth weight, higher morbidity burden, concerns for maternal health, and older parental age all were found to be correlated with increased presence in some studies but with decreased presence in others (►Table 2). These findings highlight how our secondary aim of examining these correlates of presence would be an appropriate area for the more in-depth analysis of a systematic review.…”
Section: American Journal Of Perinatologymentioning
confidence: 99%